(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the theoretical and practical aspects of using the Theory of Inventive Problem Solving (TRIZ) in the process of teaching the subject “Pedagogical Mastery.” The TRIZ methodology plays a crucial role in developing teachers’ creative and analytical thinking, as well as their ability to effectively solve pedagogical problems. The results of the study demonstrate that the application of TRIZ methods enhances the innovativeness of the educational process and contributes to the development of teachers’ professional competence.